조선시대 민사법원(法源)과 법개념 - 조선시대 민사법원의 개념화를 위하여 - 이영록(Lee, Young-Lok) (Tonga pŏphak, 2020)
이 글에서 나는 전근대 조선의 민사법원(法源)을 관인법(官人法)이라는 용어로 개념화할 것을 제안하고, 그 성격과 특징을 서술하고자 하였다. 관인법은 관인들의 의식 속에 살아있는 법으로서 구체적인 사건에서 판결에 의해 비로소 발견되는 법이다. 그것은 도덕과 분리되어 규칙으로 작용하는 엄격한 의미에서의 법은 아니었다. 그러나 개별 사안마다 어느 정도 관인들 사이에서 공유된 시비 판단의 준거로서 구속적 성격을 갖는다는 점에서는 법이라고 충분히 부를 만한 것이었다. 그런 점에서 재판관의 자의나 순전히 당사자의 합의에 기초하는 조정의 결과와는 구분되어야 함을 강조했다. 이 점은 조선민사령의 가장 근본적인 법사적 의의가 단순히 법원(法源)의 변화에 그치는 것이 아니라, 법 개념 자체의 변환에 있음을 말해 준다. 법의 근대화 이식 과정에서 나타나는 근대적 내용의 성문법과 전통에 근거한 관습법이라는 표면적 이중구조를 넘어서 사법(司法)과 법문화를 급진적으로 변화시킨 근본적인 요인이기 때문이다. I tried in this paper to propose the term ‘official’s law’ to conceptualize the source of civil law in Chosun Dynasty, and to explain what characteristics and distinctiveness it had, and how it worked as law. Official’s law meant the law which was living in consciousness of officials as judges, and was found at the moment of, and by judgments in individual cases. It was not law in the strict meaning in which law worked as rules. Nevertheless, it was qualified to be called as law in the broader meaning in that it carried binding force in each case as shared criteria of right and wrong among officials. In that respect, it was different from judge’s ad hoc, or concilliation which based on agreement of both parties. It enabled us to see that the deeper significance of Chosun Civil Ordinance(1912) lied in the change of the conception of law rather than sources of law. It was the radical factor that was at the roots of the ostensible double structure of legal sources, i.e., the coexistence the written law with modern contents, and customary law based on tradition. KCI Citation Count: 0